2018
DOI: 10.1097/wnp.0000000000000492
|View full text |Cite
|
Sign up to set email alerts
|

Interictal Epileptiform Discharge Detection in EEG in Different Practice Settings

Abstract: Inter-rater agreement among EEGers in both academic and PP settings varies considerably. Practice location, years of EFT, and board certification are associated with significantly higher performance for IED detection in routine scalp EEG. Continued medical education of PP neurologists and neurologists without EFT is needed to improve routine scalp EEG interpretation skills. The performance of automated detection algorithms is approaching that of human experts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 20 publications
(28 reference statements)
1
27
1
1
Order By: Relevance
“…33,41,42 The Persyst algorithm, although validated, has been previously associated with a high rate of false positives. 43 In its validation study, the SpikeNet algorithm was directly compared to neurophysiology-trained experts and Persyst, exceeding both in performance. 34 Here, we detected a possible relationship between spike rate and CI in hemispheres with active spikes using SpikeNet, although this possible finding requires validation in a second dataset.…”
Section: F I G U R Ementioning
confidence: 99%
“…33,41,42 The Persyst algorithm, although validated, has been previously associated with a high rate of false positives. 43 In its validation study, the SpikeNet algorithm was directly compared to neurophysiology-trained experts and Persyst, exceeding both in performance. 34 Here, we detected a possible relationship between spike rate and CI in hemispheres with active spikes using SpikeNet, although this possible finding requires validation in a second dataset.…”
Section: F I G U R Ementioning
confidence: 99%
“…Nevertheless, studies dating back several decades have reported interreader agreement on EEG findings ranging from poor to substantial but have been generally limited by factors including small EEG sample size, potentially biased selection of EEG samples (either too easy or to complex), and small numbers of readers from single centers. 1,4,5 Factors that have been correlated with improved interrater agreement for IEDs include fellowship EEG training, subspecialty board certification, academic versus private practice, and greater time devoted to EEG reading. 1,5 However, a recent study found that even expert readers with high confidence in their interpretation were often not in agreement with their peers.…”
Section: Commentarymentioning
confidence: 99%
“…1,4,5 Factors that have been correlated with improved interrater agreement for IEDs include fellowship EEG training, subspecialty board certification, academic versus private practice, and greater time devoted to EEG reading. 1,5 However, a recent study found that even expert readers with high confidence in their interpretation were often not in agreement with their peers. 6 Therefore, despite the widespread use of EEG, one could still reasonably argue the reliability of an interpretation regardless of the qualifications of the reader.…”
Section: Commentarymentioning
confidence: 99%
“…Andererseits können auch bei qualifizierten und erfahrenen EEG-Befundern beträchtliche interindividuelle Diskrepanzen in der Zuordnung von ETPs bestehen [9][10][11]. Die Übereinstimmung von zertifizieren EEG-Befundern in akademischen Institutionen mit einer EEG-Spezialausbildung ist dabei größer als die von niedergelassenen EEG-Befundern ohne Zusatzqualifikation [9,10].…”
Section: Take Home Messageunclassified